The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1128/jvi.01136-20
|View full text |Cite
|
Sign up to set email alerts
|

Classical Swine Fever Virus NproAntagonizes IRF3 To Prevent Interferon-Independent TLR3- and RIG-I-Mediated Apoptosis

Abstract: Classical swine fever virus (CSFV) is the causative agent of classical swine fever, a notifiable disease of economic importance that causes severe leukopenia, fever and haemorrhagic disease in domesticated pigs and wild boar across the globe. CSFV has been shown to antagonise the induction of type I IFN, partly through a function of its N-terminal protease (Npro) which binds IRF3 and targets it for proteasomal degradation. Additionally, Npro has been shown to antagonise apoptosis triggered by the dsRNA-homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Having observed strain dependent differences in the expression of IFN-a, we thought it necessary to investigate the type I IFN response in PRRSV-1 infected BMDM. We have previously demonstrated that dsRNA and SeV are specific agonists of TLR-3 and RIG-I mediated type I IFN responses in porcine cells, respectively (37). When utilized in BMDM, both ligands induced strong expression of the ISGs, Mx1, ISG15 and RIG-I.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Having observed strain dependent differences in the expression of IFN-a, we thought it necessary to investigate the type I IFN response in PRRSV-1 infected BMDM. We have previously demonstrated that dsRNA and SeV are specific agonists of TLR-3 and RIG-I mediated type I IFN responses in porcine cells, respectively (37). When utilized in BMDM, both ligands induced strong expression of the ISGs, Mx1, ISG15 and RIG-I.…”
Section: Discussionmentioning
confidence: 96%
“…Western blots were performed as previously described (37). Primary antibodies; Anti-RIG-I (Santa Cruz, Dallas, US #sc-376845), Anti-Mx1 (GeneTex, Hsinchu City 300 Taiwan, R.O.C., #GTX110256), Anti-ISG15 (Abcam, Cambridge, UK, #ab233071), Anti-g-tubulin (Merck, #T6557) were used where indicated.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses often evade the immune response by antagonizing specific pathways. Numerous viral proteins have been shown to antagonize the transcriptional and the RIPA activity of IRF3 ( 80 82 ). It is also tempting to speculate the viruses have coevolved to evade specific functions of IRF3, and the host can fight back using the additional options.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, STING is a target for HCV-NS4B to block RIG-I-mediated activation of IFN-β production by blocking its interaction with MAVS. NS4B and STING are localized on ER and MAM [139]. MAM-resident factor Gp78 was also found to be involved in innate antiviral signaling by targeting MAVS during vesicular stomatitis virus (VSV) infection [140].…”
Section: Other Functions Of Mamsmentioning
confidence: 99%